Molecular Identification of Extended-spectrum β-lactamase Resistant Genes in E coli Recovered from Individuals Suffered Urinary Tract-based Infection - Sara K. Al-Zubaidi (Journal of Global Pharma Technology, 2019)
The intended purpose of the current identifying study was to know the recent occurrence of E. coli-related extended-spectrum resistant-genes of blaCTX-M, blaSHV, blaTEM and blaAMPC that are responsible for community-based acquired urinary tract infection (CAUTI) and nosocomial infections (NCI). The study also was intended to reveal the genetic-based links between recovered strains. To answer these questions, non-similar 50 isolates of E. coli were recovered from UTI samples handed by 3 hospitals in Babylon City, Iraq. These samples were subjected to cultivation processes and a polymerase chain reaction technique (PCR). The resistant genes, according to PCR, were detected in 10 positive-ESBL phenotypes of the isolates. Using PCR, The blaCTX-M and blaAMPC genes were 100%-frequently identified in those 10-positive samples. However, the other genes were detected in low rates in those samples. The results, here, identify the important role of the horizontal gene transfer (HGT) in obtaining resistance by the E. coli isolates against β-lactamase-related antibiotics in Iraq. Keywords: E. coli, Extended, β-lactamase resistant genes, Spectrum.